Copper supplementation and fertility response in __ anoestrus buffaloes - A clinical trial - RANDHAWA, C S; RANDHAWA, S S; SINGH, NARINDER; SIDHU, S S (The Indian Journal of Animal Reproduction, 2023)
Clinical trial was conducted on 30 anoestrus buffaloes to study the effect of parenteral copper supplementation on the reproductive performance. Estrus was observed in 90.3 per cent (28/30) animals. Conception occurred in 63 .6 per cent (14/22) of buffaloes following subcutaneous administration of 150 mg of copper glycinate,